2014
DOI: 10.1177/0898264314558202
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in an Older Inpatient Population

Abstract: Frailty is a strong predictor of adverse outcomes in older people hospitalized with acute illness. An increased awareness of its impact may alert clinicians to screen for frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
54
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(75 citation statements)
references
References 40 publications
(52 reference statements)
9
54
2
1
Order By: Relevance
“…Further post hoc analyses suggested that the effects of the FRS on the study outcomes of time to in-hospital mortality and 30-day rehospitalization were not moderated by age (all p > .10). These findings correspond with those of prior studies (Basic & Shanley, 2015; Bellal et al, 2014; Santos-Eggimann, Cuénoud, Spagnoli, & Junod, 2009; Szanton, Allen, Seplaki, Bandeen-Roche, & Fried, 2009) and demonstrate that frailty is distinctly different from age and age-related changes that develop overtime in non-frail persons (Mansur, Colugnati, Grinsenkov, & Bastos, 2014). Further, the weak effect size we found between age and FRSs challenges the notion that frailty is unique to the aged.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further post hoc analyses suggested that the effects of the FRS on the study outcomes of time to in-hospital mortality and 30-day rehospitalization were not moderated by age (all p > .10). These findings correspond with those of prior studies (Basic & Shanley, 2015; Bellal et al, 2014; Santos-Eggimann, Cuénoud, Spagnoli, & Junod, 2009; Szanton, Allen, Seplaki, Bandeen-Roche, & Fried, 2009) and demonstrate that frailty is distinctly different from age and age-related changes that develop overtime in non-frail persons (Mansur, Colugnati, Grinsenkov, & Bastos, 2014). Further, the weak effect size we found between age and FRSs challenges the notion that frailty is unique to the aged.…”
Section: Discussionsupporting
confidence: 91%
“…Growing evidence suggests that the prevalence of frailty among hospitalized older adults is as high as 50 – 94%, depending on the instrument used (Basic & Shanley, 2015; Dent, Chapman, Howell, Piantadosi, & Visvanathan, 2014; Dent & Hoogendijk, 2014; Forti et al, 2014; Oo et al, 2013; Theou et al, 2013), and its deleterious consequences put an increased burden on patients, caregivers, and the healthcare system (Basic & Shanley, 2015; Joosten et al, 2014). In the present study, the prevalence of frailty was 68% based on a cut-off FRS of 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(92) Frailty based on a multidimensional instrument was associated with a higher likelihood of death and institutional discharge, as well as greater health-care costs. (9395) In an Australian study of older people hospitalized with an acute illness, the CSHA Clinical Frailty Scale predicted in-hospital mortality, new nursing home placement, and a longer hospital stay, (96) while a UK study found that a modified CSHA Clinical Frailty Scale (i.e., 9-point version) in adjusted analyses was an independent predictor of in-patient mortality, transfer to the geriatric service, and a length of stay of 10 or more days. (97) Another study using the 9-point version of the scale reported that moderate to severe frailty was an independent predictor of readmission to hospital or death within 30 days of discharge (adjusted OR 2.19, 95% CI 1.12–4.24).…”
Section: Discussionmentioning
confidence: 99%
“…Frailty increases with age -15.7% of adults aged 80-84 years were identified as frail compared with 26.1% of those aged 85 years and over. 2 Frailty is very common in Australian acute geriatric medicine inpatients (approximately 90%) 3 and in residents of aged-care facilities (approximately 40%, depending on country studied and scale used). 4 Frailty is a dynamic state and people can move in and out of it.…”
mentioning
confidence: 99%